Internet Marketing of Residential Properties: Investigation on Effectiveness of Its Application - Alias, Anuar; Z.T, Jeffrey Pui (Journal of Surveying, Construction and Property, 2012)
The Internet has been used so widely in many aspects of life . Lately, Website promoting and marketing of real estate has become a new wave and a new strategy. Internet eases the process of searching and matching the criteria of the house and of a buyer, however the reliability of the internet in the consumer’s eyes is a factor to be discussed. Internet buying and selling does have their pros and cons which makes the topic of buying and selling a controversial topic. The research is done on both buyer and seller respectively. Through the questionnaires answered by the buyers and sellers, perspectives and opinions are pooled and analysed. Through the research, it was found out that internet buying and selling process is done by many sellers and has already impacted the property market. The Internet has many advantages which overwhelms the disadvantages, thus it is chosen as a good tool for source of information by buyers and a good marketing tool for sellers. The prediction for future use of the internet is bright and positive through both buyers’ and sellers views It can be deduced that the future use of internet can be greatly exploited. Keywords: Internet marketing, real estate product, effectiveness, implementation.